Impact of Body Mass Index in the Cardioverter Efficacy of Amiodarone in Persistent Atrial Fibrillation - Carmen Ligero; Pau Riera; Amine El-Amrani; Victor Bazan; José M. Guerra; Silvia Herraez; Xavier Viñolas; Josep M. Alegret (Pharmaceuticals, 2024)
Background: Amiodarone is an anti-arrhythmic drug that has extensive tissue distribution and substantial storage in the fat tissue. Different studies have described some implications of body fat composition in its pharmacokinetics and pharmacodynamics. However, no clinical studies have described its implications for clinical efficacy. Methods: We studied 878 patients with persistent atrial fibrillation (AF) treated with a regimen of amiodarone and referred to electrical cardioversion (ECV), included prospectively in two Spanish registries. We analyzed the influence of body mass index (BMI), as well as overweight and obesity, in the efficacy of amiodarone for achieving pharmacologic cardioversion to sinus rhythm (SR) before ECV. Results: A total of 185 patients (21.1%) reverted to SR before ECV. Patients who reverted to SR had a lower BMI than those who did not revert (27.45 ± 4.36 kg/m2 vs. 29.11 ± 4.09 kg/m2; p < 0.001). We observed a progressively lower probability of reverting to SR in overweight and obese patients (normal weight 28.3%, overweight 21.3%, obesity 13.1%; p < 0.001). In the logistic regression, BMI (kg/m2) adjusted for other related variables remained as the main factor inversely related to reversion to SR (OR = 0.904 × kg/m2); CI 75% 0.864–0.946). Conclusions: We observed a negative relationship between an increased BMI and the efficacy of amiodarone for reversion to SR, suggesting a negative clinical impact of excess body fat in its efficacy.